MENGURAI KEMBALI MANUSIA-POLITIK ISLAM - Asri, Syamsul; Amra, Muhammad Fikri (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2023)
Muslim intelectual traditions and societies are charactericed prophetic since its inception, thus marked by specific perception and awareness about the deepest meaning of reality and its relationship with The Ultimate Truth. This perception and awareness play pivotal role in construing everyday lives of society in all aspect, including political one. Although there is no single defenition about the meaning and boundaries of islamic politics, the legacy of propfetic dimension as mentined before still play as doctrinal and operational ground of everyday islamic politics. The purpose of this paper is to shed new light on the basis for islamic politics by recentering insan kamil as a prime example of homo politics in Islam. By examining primer and secunder sources, the purpose of this paper will be reached by utilizing literatur review with content analysis on insan kamil as the role model for homo politics.